AB0745 ASSESSMENT OF DISEASE ACTIVITY USING RAPID3 AND EVALUATION OF TREATMENT EFFECT OF GUSELKUMAB IN PATIENTS WITH PSA: RESULTS FROM A RANDOMIZED PLACEBO-CONTROLLED PHASE 2 CLINICAL TRIAL. (June 2019) - Deodhar, Atul; Bruce Kirkham, L; Rahman, Proton; Helliwell, Philip; Gottlieb, Alice B.; Boehncke, Wolf-Henning; Xu, Xie L.; Han, Chenglong
Abstract : Background: Objectives: To evaluate the effect of guselkumab (GUS) on Routine assessment of Patient index Data 3 (RAPID3) in patients with psoriatic arthritis (PsA). Methods: In a phase 2 trial, patients with active PsA and ≥3% body surface area of plaque psoriasis despite current or previous treatment with standard-of-care therapies, including anti-TNFα agents, were randomized 2:1 to receive GUS 100 mg (n=100) or placebo (PBO, n=49) subcutaneously at wks 0, 4, and every 8 wks (q8w) thereafter through wk44. At wk16, patients from either group with <5% improvement from baseline in both swollen and tender joint counts were eligible for early escape to open-label ustekinumab. At wk24, all remaining PBO patients crossed-over to receive GUS 100 mg, and then received GUS at wk28 and q8w thereafter through wk44. RAPID3 (0-30) is derived from the Multi-Dimensional Health assessment Questionnaire (MDHAQ) and numerical rating scales (0-10) for pain and patient global assessment. A change of 5.1 in RAPID3 score was identified as the minimally important difference (MID) in PsA, and RAPID3 ≤3.0 was used to define PsA remission. Change in RAPID3 and proportion of patients achieving MID were compared between treatments. Correlations of RAPID3 scores with the PsA Disease activity Score (PASDAS), GRACE index, Disease activity in Psoriatic arthritis (DAPSA), and Modified Composite Psoriatic Disease activity index (mCPDAI) were evaluated using Spearman correlation. Results: The mean (SD) RAPID3 score at baseline was 16.9 (5.19). At wk24, patients in the GUS group (n=100) achieved statistically significantly greater decrease from baseline (improvement) in RAPID3 (-5.81 ± 6.0) than the PBO group (n=49) (-0.57 ± 5.1, p<0.001), and 50% of patients in the GUS group vs. 20.4% in the PBO group achieved an MID (p<0.001). Higher RAPID3 remission rate in the GUS than the PBO group (14.0% vs. 2.4%, p=0.022) was observed. The mean ±SD decrease from baseline in RAPID3 was -6.36 ±6.2 at wk24, and -7.48 ± 6.3 at wk44 in those who continued Guselkumab (N=86). Among patients who switched from PBO to GUS at wk24 (N=28), mean ± SD change from baseline (improvement) in RAPID3 was -2.28 ± 5.2 at wk24 while on placebo and -7.60 ± 6.6 at wk44 after switching to GUS. The RAPID3 score was highly correlated with PASDAS (r=0.84, p<0.001), GRACE index (r=0.89, p<0.001), DAPSA (r=0.77 p<0.001) and mCPDAI (r=0.65, p<0.001) at wk16. Conclusion: GUS-treated PsA patients demonstrated significant improvement in RAPID3 compared to PBO. RAPID3 is simple and feasible to use in routine clinical care, and it correlates well with other comprehensive PsA-specific disease activity measures. Disclosure of interests: Atul Deodhar Grant/research support from: abbVie, amgen, Eli Lilly, GSK, Janssen, Novartis, Pfizer, and UCB, Consultant for: abbVie, amgen, BMS, Eli Lilly, Janssen, Novartis, Pfizer, and UCB, L Bruce Kirkham Grant/research support from: investigator for Janssen Research & Development, LLC, Consultant for: abbvie, Eli Lilly and Company, Janssen, Novartis, Proton Rahman: None declared, Philip Helliwell Grant/research support from: Paid to charity: from abbVie, Janssen and Novartis, Consultant for: Paid to charity: from abbVie, amgen, Pfizer, and UCB and Celgene. Paid to self: from Celgene and Galapagos, alice B Gottlieb Grant/research support from: PI: incyte Corporation, Janssen-Ortho inc., Lilly ICOS LLC, Novartis, UCB, XBiotech, Consultant for: abbVie, Dermira, incyte Corporation, Lilly ICOS LLC, Novartis, Sun Pharmaceutical industries Ltd., avotres (unpaid), XBiotech (unpaid), Speakers bureau: abbVie, Eli Lilly and Company, Janssen Biotech; advisory board: Bristol-Myers Squibb, Celgene Corporation, Janssen Biotech, Janssen-Ortho inc., LEO Pharma, Novartis, UCB, Wolf-Henning Boehncke Consultant for: Pfizer inc, Speakers bureau: Pfizer inc, Xie L Xu Employee of: Employee of Janssen Research & Development, LLC, Chenglong Han Employee of: Employee of Janssen Research & Development, LLC